Implementasi Metode Dempster Shafer Untuk Mendiagnosa Penyakit Mulut Dan Kuku (PMK) Berbasis Web - Oktafiyan Pratama, Yana; Farida, Intan Nur; Dara, Made Ayu Dusea Widya (Universitas Nusantara PGRI Kediri, 2024)
Foot and mouth disease commonly known as PMK is a class of disease outbreaks that attack ruminant livestock. This virus outbreak is very bad impact among breeders. As a result of the outbreak, breeders experienced a lot of losses, both financially and in time to raise their livestock. Therefore, with the creation of a foot and mouth disease diagnostic system, it is hoped that it can help cattle breeders to deal with cows that have contracted the virus. In solving this problem the system adopts the dempster shafer method. The system can be accessed online via the internet. From the symptoms entered, the system can generate the type of disease and how to handle it.